Hubungan Perilaku Seksual dengan Motivasi Belajar Pada Remaja di SMP Negeri 1 Jatikalen Nganjuk - Rohmatun Nisa Roziana; Widyasih Sunaringtyas; Dwi Setyorini (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Youth dating patterns such as kissing, holding even sexual intercourse can have a negative impact on teenagers, especially if adolescents are still in the educational stage where they are hope for parents. The purpose of this study to determine the relationship of sexual behavior with the motivation of learning in adolescents in junior high school SMP Negeri 1 Jatikalen Nganjuk. Corelational research design with cross sectional approach with initial adolescent population in Junior High School 1 Jatikalen Nganjuk, with purposive sampling technique 48 respondents. Research result most of the respondents (75.0%) had sexual behavior in the category of low Sex Behavior, as many as 36 respondents, while most respondents (54.2%) had learning motivation in the medium category, as many as 26 respondents. The result of analysis using spearman rank test with spss known p-value = 0,036 at significant level (α) = 0,05, hence can be concluded that there is correlation between sexual behavior with motivation learn at adolescent at SMP Negeri 1 Jatikalen Nganjuk. The closeness of the relationship shows that r = -0.303 so it can be concluded that the relationship of sexual behavior with the motivation to learn in the low category which means the higher the sexual behavior, the motivation to learn tend to be low, because there are other factors that influence learning motivation. Increased libido and youth interest in the opposite sex influence the mindset so as to enhance the fantasy of the opposite sex, which in the end the mind takes more and focuses on the pleasures they make so that the motivation for learning decreases.